Large vestibular schwannomas presenting in the late state of pregnancy: a case report and literature review - Bao, Mingbin; He, Yunsen; Tao, Ye; Liu, Li; Li, Yuheng; Zhu, Yongjun; Huang, Qinjiang; Zhang, Mengjun; Wu, Bo; Wang, Hao (Frontiers in Neurology, 2023)
Vestibular schwannomas in pregnancy have rarely been reported, and there is a lack of in-depth discussion on the experience of management of massive acoustic neuromas in pregnancy. Herein, we present a pregnant woman with a giant vestibular schwannoma and obstructive hydrocephalus who presented at 30 weeks of gestation. She was initially misdiagnosed as having a pregnancy-related reaction of headache, dizziness, and vomiting that had occurred 2 months earlier. After observation at home, her symptoms progressed at 30 weeks of gestation, and imaging findings revealed a brain tumor in the CPA region with secondary cerebella tonsil herniation and obstructive hydrocephalus, and she was transferred to our center for treatment. Consequently, we relieved her hydrocephalus with a ventriculoperitoneal shunt (V-P shunt) and used corticosteroids to simulate fetal maturation. After 10 days, her mental condition deteriorated, and her right limb muscle strength gradually decreased until grade 0 (MMT Grading). Finally, under a joint consultation with the Department of Neurosurgery, Obstetrics, and Anesthesiology, she underwent a cesarean section under general anesthesia and first-stage tumor removal at 31 weeks of gestation. Upon discharge, the previously observed neurological deficits, which were reversible and had manifested during her gestational period, had been successfully resolved, and the fetus had been conserved. The neuroimaging confirmed the complete tumor removal, while the neuropathologic examination revealed a vestibular schwannoma. Therefore, we recommend early diagnosis and treatment for these patients, especially people with headaches, vomiting, and sudden hearing loss during pregnancy. Herein, we concluded that our cases provide a valuable experience in the latest acceptable time frame for the operation to prevent irreversible neurological impairment and premature delivery in late pregnancy.